Association Between Triglyceride Glucose Index and Infertility in Reproductive-Aged Women: A Cross-Sectional Study - Zhuang J; Wang S; Wang Y; Hu R; Wu Y (Dove Medical Press, 2024)
Jiaru Zhuang,1,2 Shan Wang,1 Yuan Wang,1 Renjing Hu,2 Yibo Wu1 1Human Reproductive Medicine Center, Affiliated Hospital of Jiangnan University, Wuxi, Jiangsu, 214026, People's Republic of China; 2Department of Laboratory Medicine, Jiangnan University Medical Center, Wuxi, Jiangsu, 214000, People's Republic of ChinaCorrespondence: Yibo Wu; Renjing Hu, Email 9862016107@jiangnan.edu.cn; weiweihuhu112@163.comPurpose: In recent years, female infertility has become a research hotspot in the field of health management, and its cause may be related to insulin resistance (IR). We used a novel and practical IR indicator, the TyG index to explore its association with infertility.Patients and Methods: We calculated the TyG index using data from adult women who participated in the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018. Then, we used multivariate logistic regression, smooth curve fitting, and subgroup analysis to examine the association between the TyG index and infertility in women.Results: Logistic regression models showed a positive correlation between the TyG index and infertility, which remained significant even after adjusting for all confounders (OR=1.51,95% CI:1.14- 2.00, p=0.005). This association was consistent in all subgroups (age, education level, marital status, BMI, smoking, alcohol consumption, hypertension, diabetes, pelvic inflammatory disease/PID treatment, and menstrual regularity in the past 12 months) (p> 0.05 for all interactions). However, the diagnostic power of the TyG index for infertility was limited (AUC=0.56, 95% CI: 0.52- 0.61).Conclusion: The TyG index is positively correlated with infertility, but its diagnostic value is limited. Further research is needed on the TyG index as an early predictor of infertility.Keywords: cross-sectional study, NHANES, infertility, insulin resistance, triglyceride glucose index, TyG